PENAMPILAN BEBERAPA VARIETAS TOMAT PADA DUA KONDISI LINGKUNGAN - Pongoh, Jantje (Universitas Sam Ratulangi, 2011)
Increasing tomato production could be approach by various ways such as intensification and extensification programs. The programs should be supported by availability of seeds and good varieties produced by breeder. Department of Agriculture has released several high yielding varieties. Tomato grows in a variety of altitude, both the highlands and lowlands, depending on variety. Therefore, ability of adaptation on specific location of tomato variety should be assessed. In relation to that, performance of six tomato varieties was evaluated on two different environments. The experiment was used factorial design. The results showed that performance some varieties varied between the two different environments. Alista variety and Victory F1 revelead good performance on characters fruit weight and fruit diameter.This two varieties could be used for breeding material. Tomatoes planted on double row space showed better performance then others. Genetic similirity pattern on different row space was resulting different response. Keywords : Performance, variety, environment, similirity